Simple method for determining the size of the ProSeal laryngeal mask airway in children: a prospective observational study - Haliloglu,Murat (2017)
Abstract Background and objectives: The size of the ProSeal laryngeal mask airway in children is determined by the patient's weight. However, in some instances, an alternative method may be required. This study aimed to compare sizing by the auricle with conventional ProSeal laryngeal mask airway sizing by weight in children. Methods: After approval by the institutional ethics board and written informed consent from parents, 197 children with American Society of Anesthesiologists physical status I-II who were scheduled for a routine genitourinary operation were included in the study. The correct ProSeal laryngeal mask airway size was determined according to the size of the auricle in children. The results were compared with the standard weight-based method recommended by the manufacturer's guidelines. The patients were classified into different groups depending on the ProSeal laryngeal mask airway sizes as determined by both methods. Agreement between both techniques was evaluated with κ coefficient statistics. Results: Insertion and adequate ventilation were achieved in 185 patients at the first attempt, and 12 patients required a second attempt. Three patients had to be intubated. Agreement between the two methods of size selection of the ProSeal laryngeal mask airway was moderate using κ statistics. Conclusions: Choosing the size of the ProSeal laryngeal mask airway in children according to the auricle of the child is valid and practical. In particular, this is an alternative method in situations where the patient's weight is unknown, such as in emergency situations.